IUD use Lippes in a marginal community of Lima - Guardia S., Guillermo (2015)
The family planning project through a program of maternal and child health began 34 months ago in Pamplona Alta. For initiation of the work was performed in October 1966 a census and Social Survey on family composition and attitudes about family planning.